Analysis of Work Motivation, Competency and Job Satisfaction on The Performance Of Dental and Oral Therapists In Puskesmas Surabaya City - Widiastuti , Kuntarti; Camalia , Leena Qonita; Triana, Dewi; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (INNOVATION RESEARCH JOURNAL, 2025)
This research is to analyze the effect of Work Motivation, Competency, and Job Satisfaction on the Performance of Dental and Oral Therapists in all Puskesmas in Surabaya. The research method used is a quantitative method. The population in this study was all Dental and Oral Therapy at all Puskesmas in Surabaya, totaling 54 people. The sampling technique used a total sample of 54 Dental and Oral Therapy people. The data analysis technique is multiple linear regression analysis and processed using SPSS. The results of the research show that 1) Work Motivation has a significant effect on the performance of Dental and Oral Therapists in all Puskesmas in Surabaya., 2) Competency has a significant on the performance of Dental and Oral Therapists in all Puskesmas in Surabaya, 3) Job Satisfaction has a significant effect on the performance of Dental and Oral Therapists in all Puskesmas in Surabaya, 4) Simultaneous test of the variables Work Motivation, Competency and Job Satisfaction have a significant effect on the performance of Dental and Oral Therapists at all Puskesmas in Surabaya, 5) Competency has a dominant effect on the performance of Dental and Oral Therapists at all Puskesmas in Surabaya